GENDER AND VIOLENCE: A RISING ISSUE - A. Saghir; H. Tabassum; M. Amir; S. Arshad A. Cheema; S. Cheema (Journal of Animal and Plant Sciences, 2011)
Women status in Pakistan is not conspicuous in any discipline of the life. Gender violence is pervasive and persistent, cutting across divisions of class, caste, age and community. Gender based violence is perpetrated at many different levels, i.e. at the family, community and state levels, and in many different forms. The fear of violence perpetuates a state of insecurity; a feeling of insecurity undermines a women confidence, besides affecting her access to resources and overall quality of life. Women have specific problems, which must be catered for. The present study was conducted through random sampling by 150 married women. All the rural women of Tehsil Faisalabad were included in the sampling frame. The data was collected through pre-tested and validated interview schedule and then was analyzed by using Statistical Package for Social Sciences (SPSS) to draw conclusions and to suggest measures for improvement. It was found from the study that violence has different forms such as, physical, verbal, mobility, psychological, social and economic. All these forms impacted an adverse affect on women’s life at various stages. Government, social groups, theologians and organizations should play their role in discouraging such behaviours.
Keywords: gender; violence; and womens issue